2019
DOI: 10.1101/632562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of biochemically neutral positions in liver pyruvate kinase

Abstract: In the goal of interpreting human exomes, when predictive programs assign functional importance to some positions, they implicitly assume the existence of non-important positions -those that accommodate many side chain chemistries without altering function ("neutral"). However, very few (if any) experimental studies have demonstrated the existence of neutral positions. We sought experimental evidence for neutral positions using human liver pyruvate kinase (hLPYK) as a model system. To that end, we used multipl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(44 citation statements)
references
References 61 publications
1
43
0
Order By: Relevance
“…Empirically, for datasets the size of the hLPYK set, we have found that rheostat scores above 0.5 indicate strong rheostat character of the position 3 . In contrast to rheostat scores, neutral scores must be above 0.7 to be considered a high score 12 . For toggle scores, we previously defined a strong toggle threshold of "at least 8 severe variants" 14 The results from this study confirm that substitutions distant to the two allostericallycoupled binding sites can exert full tunability over allosteric coupling (e.g., full bin occupancies in Figure 4 and rheostat scores of 1 in Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, for datasets the size of the hLPYK set, we have found that rheostat scores above 0.5 indicate strong rheostat character of the position 3 . In contrast to rheostat scores, neutral scores must be above 0.7 to be considered a high score 12 . For toggle scores, we previously defined a strong toggle threshold of "at least 8 severe variants" 14 The results from this study confirm that substitutions distant to the two allostericallycoupled binding sites can exert full tunability over allosteric coupling (e.g., full bin occupancies in Figure 4 and rheostat scores of 1 in Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the appropriate width and number of histogram bins, the RheoScale calculator assessed the full experimental dataset for (i)minimal and maximal values for the parameter being assessed, (ii) average error of experimental measurements, and (iii) average number of variants available per position. Since completing our first study of "local" hLPYK rheostat positions 3 , we have obtained and collated a much larger dataset of hLPYK parameters and used them to refine RheoScale histogram analyses 12,13 . These include measurements for additional variants and multiple, independent measurements of wildtype hLPYK (Supplemental Information).…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7] As such, substitutions at these "rheostat" positions provide ready opportunities for fine-tuning function during evolution and protein engineering. The rheostat substitution behavior is strikingly different from (i) positions for which most substitutions abolish function (a "toggle" substitution outcome; e.g., 2 ) and (ii) positions that can accommodate a range of substitutions without any change in protein function (a "neutral" substitution outcome; e.g., 8 ). Both toggle and neutral positions are often associated with their own evolutionary signatures: conserved positions are expected to exhibit toggle substitution behavior, whereas highly nonconserved positions may be expected to exhibit neutral substitution behavior.…”
Section: Introductionmentioning
confidence: 90%
“…The lower structures show two views of the structure of a single monomer, with stars approximating the locations of the active (yellow), allosteric inhibitor (green), and allosteric activator (cyan) sites. Magenta spheres identify positions with strong phylogeny scores tested in this study: 107, 177, 192, 259, 107, 423, and 538 thresholds for the rheostat, toggle, and neutral scores that were used to assign an overall substitution behavior to each position 2,4,8 ; those thresholds are indicated in Figure 3 by dashed horizontal lines.…”
Section: Biochemical Testing Of Substitution Outcomes For Phylogenetic Positions In Hlpyk Positionsmentioning
confidence: 99%
See 1 more Smart Citation